2018
DOI: 10.3889/oamjms.2018.385
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Effects of Dexmedetomidine and Propofol in Controlling the Hemodynamic Responses after Intubation: A Double-Blind, Randomized, Clinical Trial Study

Abstract: AIM:This study aimed to compare the effects of dexmedetomidine and propofol in controlling the hemodynamic response following intubation of patients’ candidate intubation in the emergency departmentMETHODS:A total of 114 patients were randomly assigned to one of 2 groups to receive one of the following treatments: dexmedetomidine 0.4 µg/kg (Group D, n = 57) and propofol 1–1.5 mg/kg/h (Group P, n = 57). Hemodynamic data such as the systolic blood pressure, diastolic blood pressure, arterial oxygen saturation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…In their study the dose of fentanyl used was 1 µg/kg whereas we used it in higher dose that is 2 µg/kg which might be the reason for the difference in the result of our study. Alireza et al 23 compared dexmedetomidine and propofol in controlling the hemodynamic response following intubation in the patients in the emergency department. They used dexmedetomidine in a dose of 0.4 µg/kg.…”
Section: Similarlymentioning
confidence: 99%
“…In their study the dose of fentanyl used was 1 µg/kg whereas we used it in higher dose that is 2 µg/kg which might be the reason for the difference in the result of our study. Alireza et al 23 compared dexmedetomidine and propofol in controlling the hemodynamic response following intubation in the patients in the emergency department. They used dexmedetomidine in a dose of 0.4 µg/kg.…”
Section: Similarlymentioning
confidence: 99%
“…In surgical application, dexmedetomidine is administered to maintain the balance of hemodynamic factors and provide effective analgesia; this helps reduce the use of anesthetics [ 1 , 2 ]. For patients with endotracheal intubation under general anesthesia, it can maintain hemodynamic stability, facilitate intraoperative management, and reduce the occurrence of serious cardiac accidents, including myocardial ischemia in surgical patients with cardiovascular disease [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…This could suggest our primary endpoint of 30 minutes from infusion was not optimal, despite previous reports. 9,10…”
Section: Discussionmentioning
confidence: 99%
“…Several studies evaluated hemodynamic effects of propofol in non-TTM patients and found hypotension was seen within 30 minutes of propofol introduction. 9,10 During TTM drug distribution may be limited and metabolism and excretion may be decreased, thus perpetuating drug effects in an unpredictable manner. 11 These alterations have been attributed to drug distribution to central and peripheral compartments and reduction in hepatic blood flow.…”
Section: Introductionmentioning
confidence: 99%